2016
DOI: 10.1103/physrevb.94.035203
|View full text |Cite
|
Sign up to set email alerts
|

Output polarization characteristics of a GaN microcavity diode polariton laser

Abstract: We report the steady state output polarization characteristics of GaN-based microcavity polariton lasers operated with electrical injection at room temperature. The output is unpolarized below the non-linear threshold injection current and is linearly polarized above it with a maximum degree of polarization of ~ 22 %. The results have been analyzed theoretically and the calculated results are in agreement with the measured data. We have also measured the polarization resolved output light-current characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
(72 reference statements)
3
11
0
Order By: Relevance
“…[9] and electrically [10]. In the case of optical excitation, it is also possible to obtain a circularly polarized output above threshold and this behavior has been verified experimentally in the steady state at cryogenic temperatures [12][13][14][15].…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…[9] and electrically [10]. In the case of optical excitation, it is also possible to obtain a circularly polarized output above threshold and this behavior has been verified experimentally in the steady state at cryogenic temperatures [12][13][14][15].…”
mentioning
confidence: 82%
“…However, it has been experimentally demonstrated that the orientation of this polarization is stochastic and hence the polarization cannot be experimentally recorded in the steady state [4,5]. Linear polarization can be observed in the steady state output only by pinning along a preferred crystallographic axis [6][7][8][9][10] and the degree of polarization decreases at high pumping levels due to the depinning effect caused by polariton-polariton repulsive interactions and self-induced Larmor precession of the Stokes vector of the condensate [11].These trends in the linear polarization have been observed in polariton lasers pumped optically[9] and electrically [10]. In the case of optical excitation, it is also possible to obtain a circularly polarized output above threshold and this behavior has been verified experimentally in the steady state at cryogenic temperatures [12][13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The supercell size is kept 25 Å to prevent the interaction between the adjacent periodic images of the nanocluster. Further, we have employed ab initio atomistic thermodynamics to identify thermodynamically the most favorable configuration/structure at ambient conditions (T=300K, po = 1atm) [33][34][35][36]. The size of the nanocluster (used in our simulations) is taken considering the thickness of the films as in our experiment.…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…Banerjee and Majhi [30] studied the Hawking radiation process by using quantum tunneling phenomenon at horizons and investigated the back-reaction effects. The quantum tunneling spectrum for scalar and fermion particles has also been discussed in literature [31]- [35].…”
Section: Introductionmentioning
confidence: 99%